КЕРУВАННЯ ВАНТАЖОПІДЙОМНИМ ПРИСТРОЄМ КРАНА-МАНІПУЛЯТОРА ПІД ЧАС ОПУСКАННЯ ВАНТАЖУ У ВАННУ З АГРЕСИВНОЮ РІДИНОЮ - Толочко, О.І.; Стяжкін, В.П.; Рижков, О.М. (Інститут електродинаміки НАН України, Київ, 2020)
The paper analyses mathematical model for hoisting mechanism of overhead crane manipulator. This crane is expected to operate in waste processing plant in process of deactivation metal. The hoisting mechanism has the form of telescopic column. This column used to submerging basket full of polluted scrap metal in bath with deactivation substance. The model takes into account changes of static torque resistance and motor inertia. The torque resistance change is produced by buoyancy force when basket with load submerging and motor inertia when basket detached from column after sinking to the bath bottom. Results of Simulink modelling showed point to use position control systems. References 7, figures 7.